Rahima’s Knot: Women Ulema Act to Respond the Situation of Community during Covid-19 Pandemic - Andi Nur Faizah (Yayasan Jurnal Perempuan, 2020)
This paper aims to examine the autonomy and power of women ulema in responding to the community situation during the Covid-19 pandemic. Women ulema or what is called Rahima's knot in the writing refer to ulema who are female, have attended a series of women ulema education, have a community base, and have a gender justice based on Islamic perspective. Data was collected through a focused group discussion (FGD) conducted by Rahima on representatives of Rahima’s knot in West Java, Central Java, East Java, as well as online observations. The findings of this study are the self-autonomy of women ulema is related to self-position, access to networks, and community conditions. The initiatives carried out by women ulema in the form of quick response assistance and preaching through online are part of the strength that is used to strengthen the community. The women's collective power is seen prominently in Rahima's knot on the basis of majelis taklim women through community economic empowerment. Keywords: women ulema, Rahima’s knot, Covid-19 pandemic, autonomy, power